Rehabilitation activities for children with posture disorders - Homola, Alona; Stashenko, Natalia; Karpenko, Mykola (The Ukrainian Scientific Medical Youth Journal)
according to the World Health Organization, 20-30% of people in the world have diseases and disorders of the musculoskeletal system, which are accompanied by: scootiness, discomfort, reduced walking amplitude and painful sensations. With scientific progress there are new perspectives, but there is another side of negative factors associated with a small-duty way of life and lack of manual activity. During the day: sitting at the table, in front of the computer, with the phone hand, violating the rule of “student position” by being in an uncomfortable position for more than 1 – 2 hours. These factors contribute to gipotonichy muscles and lead to the formation of imbalances of the spinal musculature, eventually develop degenerative-dystrophic diseases of the musculoskeletal apparatus. Analysis of skinning of early diagnostics of changes and deformations of the posture in adolescence. The problematics of the XXI century themes is not new. Analyzing scientific articles on the topic of postural disorders, one should pay attention to the fact that the main efforts are aimed at improving health and preventing diseases. This will ensure the proper level of health and reduce the incidence of diseases in the population. Objective description. This publication analyzes the results of preventive and diagnostic examinations, carried out by preadolescent patients with postural disorders in the sagittal and frontal planes. Materials and methods. The results of prophylactic and diagnostic review were analyzed, in the city of Kiev, the Communal non-profit organization "Consultative and Diagnostic Center" of the Svyatoshinsky district, Phil 2, from May to July 2022. Participated 490 children of preadolescent age, 11 - 15 years, with impaired position in the sagittal and frontal areas. With consent of parents or guardians. The following examination methods were used: visual diagnostics, somatoscopy, manual and musculoskeletal testing, functional tests to determine the stages of positional disorders, X-ray and magnetic resonance imaging. For convenience, the documentation is formed, and the patient card is developed. The majority of the patients with impaired posture in the sagittal and frontal planes are treated by conservative methods. Conclusions. The main purpose of the preventive-diagnostic examination is to detect skeletal and muscular imbalances at the initial stage, to choose active procedures, to follow recommendations for elimination of negative body movements during the day. The child’s health depends on the constant monitoring of parents and consultations of doctors. There should be cooperation of physicians, parents and children, observance of simple rules and prophylactic measures.